Massive Pleural Effusion as the Initial Manifestation of Pulmonary Tuberculosis in an Adolescent: A Case Report - Febriyanti Angghita Putri Duarsa; I Gusti Putu Ayu Susilawati Wida Lestari; Putu Siska Suryaningsih (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Tuberculosis remains a major global health problem and may present with nonspecific manifestations in adolescents, including pleural effusion, which can complicate diagnosis. Massive pleural effusion as an initial manifestation of pulmonary tuberculosis is uncommon and requires prompt diagnostic evaluation. Case Report: A 15-year-old male adolescent presented with progressive dyspnea, cough, intermittent fever for more than two weeks, decreased appetite, and weight loss. Physical examination revealed decreased breath sounds and stony dullness over the right hemithorax. Chest radiography showed massive right pleural effusion with mediastinal shift. Initial thoracentesis produced approximately 1,600 mL of seroxanthochromic fluid, with a total drainage volume of 2,850 mL following repeated aspiration. Pleural fluid analysis confirmed an exudative effusion with protein 5.1 g/dL and lactate dehydrogenase 1,100 U/L. Molecular testing of pleural fluid detected Mycobacterium tuberculosis at a trace level without rifampicin resistance. The patient received first-line anti-tuberculosis therapy and supportive treatment, resulting in gradual clinical improvement during an 8-day hospitalization. Discussion: This case shows the importance of combining clinical, radiological, pleural fluid, and molecular findings to diagnose pleural tuberculosis. Early molecular testing supported prompt treatment initiation and favorable clinical recovery. Conclusion: Massive pleural effusion in adolescents should raise suspicion for tuberculosis, particularly in endemic areas. Early diagnosis and timely anti-tuberculosis therapy are essential to improve outcomes and prevent complications